Middle permian (Guadalupian) brachiopods from the Xiujimqinqi area, Inner Mongolia, northeast China, and their palaeobiogeographical and palaeogeographical significance - Guang Shi; S Shen; JI Tazawa (2002)
A small brachiopod fauna is described from the lower part of the Xiujimqinqi Formation of the Xiujimqinqi area in central-east Inner Mongolia, northeast China. The age of this fauna is regarded as Wordian (Middle Guadalupian, Middle Permian) by comparison with a similar brachiopod fauna from the Zhesi area of central Inner Mongolia, and by constraints from fusulinaceans associated with the Zhesi fauna. The Xiujimqinqi fauna is typical of mixed Boreal/Palaeoequatorial Middle Permian brachiopod faunas of East Asia. The mixed nature of these faunas is interpreted to have resulted from the combined effects of a middle palaeolatitudinal position, intensified plate convergence between Sino-Korea and Mongolia, and sea surface current connections with both the Arctic Sea in the north and eastern Palaeo-Tethys to the south. Possible Kaninospirifer is reported for the first time from China.